2018
DOI: 10.1097/mph.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Infiltration of Cryopreserved Ovarian Tissue in 2 Patients With Ewing Sarcoma

Abstract: We report the clinical history of 2 female patients with Ewing sarcoma and microscopic ovarian infiltration. In both cases, the initial workup found no metastasis. However, the examination of cryopreserved ovarian tissues revealed the presence of CD99 positive tumor cells with rearrangement of EWS gene confirmed by FISH. Both children were treated as patients with localized tumor and are currently in remission. These reports underline that, in Ewing sarcoma patients, retransplantation of cryopreserved ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Abir et al [ 27 ] analyzed the ovarian tissue from eight Ewing’s sarcoma patients and found evidence of ovarian involvement in one patient by RT-PCR amplification of the ES specific translocation transcript. Infiltration of ovarian tissue cryopreserved for fertility preservation purposes with ES was also described in two young patients, based on the presence of CD99 positive tumor cells harboring the EWS-FLI1 translocation [ 28 ]. Although these studies suggest that ovarian involvement in ES is relatively rare, the frequency at which ovarian tissue fragments are contaminated with ES cells might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abir et al [ 27 ] analyzed the ovarian tissue from eight Ewing’s sarcoma patients and found evidence of ovarian involvement in one patient by RT-PCR amplification of the ES specific translocation transcript. Infiltration of ovarian tissue cryopreserved for fertility preservation purposes with ES was also described in two young patients, based on the presence of CD99 positive tumor cells harboring the EWS-FLI1 translocation [ 28 ]. Although these studies suggest that ovarian involvement in ES is relatively rare, the frequency at which ovarian tissue fragments are contaminated with ES cells might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Greve et al [ 21 ] malignant cells were not detected in ovarian tissue stored for fertility preservation of nine surviving ES patients. Despite that metastatic involvement of the ovaries is not common, infiltration of ovarian tissue with ES has been reported by several authors [ 22 , 23 , 24 , 25 , 26 ], also in the context of OTC [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of metastatic ovarian involvement in EWS patients have been described in the literature [3,24]. Microscopic ovarian infiltration could be present in non-metastatic EWS [14]. No metastasis in TT has been described [25].…”
Section: Discussionmentioning
confidence: 99%
“…EWS MRD detection by RT-PCR has been performed in OT. Schifflers et al [14] studied MRD in OT from patients with non-metastatic EWS. Abir et al described EWS MRD detection of cryopreserved ovarian samples by snap freezing [15].…”
Section: Introductionmentioning
confidence: 99%
“…The family understood that prognosis for survival was poor 17,18 . Furthermore, they understood the risk of reintroducing cancer cells with autotransplantation 19 . However, this risk is thought to be low for rhabdomyosarcoma, and better methods of screening ovarian tissue for residual disease as well as in vitro maturation and fertilization technology may be available in the future 20 .…”
Section: Casementioning
confidence: 99%